Securing the rights and health of domestic workers: the importance of ratifying the ILO's C189 - Andrian Liem; Sabina Satriyani Puspita; Fajar; Lita Anggraini (BMC, 2024)
Abstract This commentary highlights the critical importance of ratifying the International Labour Organization's (ILO) Domestic Workers Convention No. 189-2011 (C189) to secure the rights and health of domestic workers (DWs) worldwide, particularly in light of the World Health Organization's World Health Day 2024 theme 'My Health, My Right'. The ILO's C189 represents a significant advancement in labour rights, offering protection to a highly feminised sector where women make up 80% of the estimated 50-100 million DWs worldwide. The ILO's C189 aims to address the marginalisation and exploitation that DWs have historically faced by ensuring that they receive the same protections as other workers. This encompasses measures against abuse, harassment and violence, and the establishment of a secure and healthy working environment, as outlined in Article 13. The commentary emphasises the urgent need for the enactment of legal frameworks in countries such as Indonesia, where many of the approximately 10 million DWs encounter shocking abuses both within the country and abroad. The ratification of the C189 and the enactment of national laws, such as Indonesia's Draft Law on the Protection of Domestic Workers (RUU PPRT), are essential for the safeguarding of the rights and health of DWs. The commentary compares Indonesia with the Philippines, as the latter has been a signatory to the C189 since 2012 and has enacted its National Domestic Workers Act in 2013. The ratification of the C189, therefore, is imperative for igniting the protection and advancement of labour rights for DWs globally. This ILO's C189 represents a significant first step in addressing the long-standing and complex issues of marginalisation and exploitation prevalent in this predominantly female sector. It is also essential that the potential obstacles and concerns related to the ratification and implementation of the ILO's C189 are addressed collaboratively by stakeholders and not viewed as justifications for inaction.